Blood vessel control of macrophage maturation promotes arteriogenesis in ischemia - Krishnasamy, Kashyap Narayan; Lozanovski, Vladimir J. (Nature Communications, 2017)
Ischemia causes an inflammatory response that is intended to restore perfusion and homeostasis yet often aggravates damage. Here we show, using conditional genetic deletion strategies together with adoptive cell transfer experiments in a mouse model of hind limb ischemia, that blood vessels control macrophage differentiation and maturation from recruited monocytes via Notch signaling, which in turn promotes arteriogenesis and tissue repair. Macrophage maturation is controlled by Notch ligand Dll1 expressed in vascular endothelial cells of arteries and requires macrophage canonical Notch signaling via Rbpj, which simultaneously suppresses an inflammatory macrophage fate. Conversely, conditional mutant mice lacking Dll1 or Rbpj show proliferation and transient accumulation of inflammatory macrophages, which antagonizes arteriogenesis and tissue repair. Furthermore, the effects of Notch are sufficient to generate mature macrophages from monocytes ex vivo that display a stable anti-inflammatory phenotype when challenged with pro-inflammatory stimuli. Thus, angiocrine Notch signaling fosters macrophage maturation during ischemia., Molecular mechanisms of macrophage-mediated regulation of artery growth in response to ischemia are poorly understood. Here the authors show that vascular endothelium controls macrophage maturation and differentiation via Notch signaling, which in turn promotes arteriogenesis and ischemic tissue recovery.